Self esteem among college students: a study of satisfaction of basic psychological needs and some variables - ÜMMET, DURMUŞ (ELSEVIER SCIENCE BV, 2015)
The aim of this study is to examine college students' self esteem according to the satisfaction of their basic psychological needs and some certain variances. The sample of the study consisted of 342 students studying in college. The data was collected through Coopersmith Self Esteem Inventroy, Basic Psychological Needs Scale and an information form developed by the researcher. When the obtained data was examined, it was found that the satisfaction of autonomy and relatedness needs of the students significantly predicted their self esteem, while the satisfaction of competence need did not predict self esteem. Also, self esteem of the students showed significant difference as to educational level of mother, income level and perceived parent attitudes by them, whereas educational level of father and gender did not have effect on self esteem.
Keywords: Self esteem; Satisfaction of Basic Psychological Needs; College Students; AUTONOMY; MOTIVATION